2007
DOI: 10.1089/rej.2006.0535
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the Heart and Liver During Normal Aging and Calorie Restriction

Abstract: Autophagy is a highly regulated intracellular process for the degradation of cellular constituents and essential for the maintenance of a healthy cell. We evaluated the effects of age and life-long calorie restriction on autophagy in heart and liver of young (6 months) and old (26 months) Fisher 344 rats. We observed that the occurrence of autophagic vacuoles was higher in heart than liver. The occurrence of autophagic vacuoles was not affected by age in either tissue, but was increased with calorie restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
124
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 59 publications
11
124
1
Order By: Relevance
“…In this study, we found that expression of Atg7 and LC3/Atg8 was significantly decreased in aged rat kidneys, whereas there was no marked change in the expression of Atg5. These results are consistent with a previous study that reported a decrease in Atg7 expression in older rat hearts (Wohlgemuth et al 2007). Isolated mitochondria obtained from Atg7 −/− skeletal muscle cells exhibit a significant defect in mitochondrial respiration, indicating that there is a close relationship between autophagy, oxidative stress, and aging (Wu et al 2009a).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, we found that expression of Atg7 and LC3/Atg8 was significantly decreased in aged rat kidneys, whereas there was no marked change in the expression of Atg5. These results are consistent with a previous study that reported a decrease in Atg7 expression in older rat hearts (Wohlgemuth et al 2007). Isolated mitochondria obtained from Atg7 −/− skeletal muscle cells exhibit a significant defect in mitochondrial respiration, indicating that there is a close relationship between autophagy, oxidative stress, and aging (Wu et al 2009a).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, we also indicated that protein expression of beclin-1/Atg6 was slightly but not significantly increased in the aged rat kidneys, which is in line with the earlier report (Kume et al 2010). Previous studies have found that beclin-1 has a significant increase in the aged rat heart (Wohlgemuth et al 2007) and skeletal muscle (Wohlgemuth et al 2010). Changes in beclin-1 are tissue and cell context dependent.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…28 However, there is a contradicting report that autophagy in the heart and liver do not decrease with age in ad libitum-fed rats and is enhanced by caloric restriction in the heart. 29 There are few reports examining autophagy in the aging kidney. Our examination showed that the expression of beclin 1, which has a significant role in autophagy, 30 was increased compared with that in young rat kidney (Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%